Biochemical Changes Induced by the Pesticide Thiacloprid in Rats: The Protective Role of Curcumin Against Environmental Pollutants - Taif Muslim (Journal of Health and Biology, 2026)
This study assessed how effective curcumin is against Thiacloprid toxicity in male rats. Thiacloprid exposure led to obvious oxidative stress, indication showing the significantly increased levels of lipid peroxidation, diminished GSH levels, and severely inhibited activities of the enzymatic antioxidant defense system. In addition, Thiacloprid altered plasma pituitary-gonadal hormones, induced testicular histopathological changes and caused a significant reduction in sperm parameters (sperm count, motility, viability), combined with systemic hepatotoxicity and biochemical derangement. On the other hand, co-administration of Curcumin ameliorated these toxicological hazards by harmonizing cellular redox equilibrium as well as enhancing antioxidant enzyme activities, maintaining histopathology of testicular architecture and modulating hormonal and biochemical parameters. These findings demonstrate the potent therapeutic potential of Curcumin as a natural protective bioprotectant against pesticide-induced organ toxicity and reproductive failure.